The Constitutional and International Dimensions of the European Convention on Human Rights: دراسة تحليلية - نجم الدين ز‌نگنه‌, إسماعيل; انور احمد, دژوار; رشيد آغا, هێمن (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The adoption of the European Convention on Human Rights in 1950, and came into force in 1953; to a large extent led to the establishment of a fundamental phase in the European Union. It transferred the Union from an agreement between states to unification amongst people primarily concerned with the protection of human rights and freedoms in the region. This protection of human rights and freedoms was supposed to be and rded a monopoly arena for the states’ internal sovereignty. Hence, this research has great importance when attempting to legally apply the agreement and considering it as an international agreement within the framework of International Law or texts that contest or surpass the constitutional texts. This research endeavors through following an analytical methodology to clarify the contents of the agreement and its relations with the European Union. Further, it clarifies its impact on the member states of the agreement and others, and then examining the aspects that highlight the international and constitutional aspect of the agreement. The techniques used to represent the research effectively originates from the framework of a research structure compatible with the problematic studies of research and its methodology.